2014
DOI: 10.1007/s10212-014-0220-y
|View full text |Cite
|
Sign up to set email alerts
|

Stimulating positive emotional experiences in mathematics learning: influence of situational and personal factors

Abstract: PostprintThis is the accepted version of a paper published in European Journal of Psychology of Education. This paper has been peer-reviewed but does not include the final publisher proof-corrections or journal pagination. The study aims to assess the relative importance of a large number of variables for predicting students' positive activating emotions during mathematics learning. Participants were 668 firstyear upper secondary school students from 33 schools of different sizes and locations. Two questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 43 publications
(67 reference statements)
3
13
0
Order By: Relevance
“…That the two-goal model was found to be most appropriate for the Swedish sample is in accordance with our previous studies on Swedish students, using partially different instruments and in different cohorts (Grades 5-12, sample size varying between 600 and 5600; Palm, Sullivan Hellgren, & Winberg, 2010;Winberg et al, 2014;Winberg & Palm, 2016). In addition, a recent thesis by Blomgren (2016), to our knowledge the only other Swedish study examining the factor structure of achievement goals, reports the same problem with separating Swedish students' PAp and PAv goals.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…That the two-goal model was found to be most appropriate for the Swedish sample is in accordance with our previous studies on Swedish students, using partially different instruments and in different cohorts (Grades 5-12, sample size varying between 600 and 5600; Palm, Sullivan Hellgren, & Winberg, 2010;Winberg et al, 2014;Winberg & Palm, 2016). In addition, a recent thesis by Blomgren (2016), to our knowledge the only other Swedish study examining the factor structure of achievement goals, reports the same problem with separating Swedish students' PAp and PAv goals.…”
Section: Discussionsupporting
confidence: 88%
“…MAp goals have been shown to correlate positively with interest (Church, Elliot, & Gable, 2001), use of productive learning strategies (Wolters, 2004), positive emotions (Winberg, Hellgren, & Palm, 2014), and high effort (Wolters, 2004). PAv goals show overall unfavorable patterns of outcomes (Church et al, 2001;Elliot & Church, 1997;Elliot & McGregor, 2001;Wolters, 2004), whereas the results for PAp goals are more mixed.…”
Section: Achievement Goalsmentioning
confidence: 99%
“…A high level of perceived teacher enthusiasm and autonomy support further improves college students’ perceived task value in class-related learning, which eventually results in lower class-related boredom and other positive learning outcomes. As situational factors, teacher enthusiasm and autonomy support were found to be important predictors of class-related boredom, considering the reciprocal relationship between positive and negative emotions ( Cacioppo and Berntson, 1994 ; Schimmack, 2001 ; Smith et al, 2006 ; Schimmack and Colcombe, 2007 ), which is aligned with the research results of Winberg et al (2014) on positive emotions. Our results also showed that perceived autonomy support and perceived task value fully mediated the relationship between perceived teacher enthusiasm on class-related boredom as serial and parallel inductors, which suggests the importance of the two mediators in this process.…”
Section: Discussionsupporting
confidence: 72%
“…One contribution in this special issue reports that students' interest differed between problems with a connection to reality ("dressed up" word problems and modelling problems) and problems without a connection to reality (intra-mathematical problems) when controlling for task difficulty (Rellensmann and Schukajlow 2017). As students' emotions such as enjoyment and boredom are related to their interest (Pekrun et al 2011;Tulis and Ainley 2011;Schukajlow and Rakoczy 2016;Winberg et al 2014), similar differences can also be expected for students' emotions. Taken together, we argue that task contents and domains should be considered to a greater extent in research on emotions and motivation in education, as emotions and motivation have been shown to be content-specific (Rakoczy 2008; and domain-specific (Goetz et al 2007).…”
Section: Trends In Research On Emotions and Motivation In Mathematicsmentioning
confidence: 97%